Foundations of athletic training prevention, assessment, and management - Anderson, Marcia K. (Lippincott Williams & Wilkins, 2013)
"This text integrates basic medical concepts and related scientific information to provide a strong foundation of general athletic training practices. Using a problem-solving approach to prevention, recognition, assessment, management, and disposition of sports-related injuries and diseases, this text provides athletic trainers and athletic training students with the most extensive, challenging content in a user-friendly format. New Content - This edition features a new chapter on Psychological Intervention Strategies"--Provided by publisher